Abelia x grandiflora - Edward F. Gilman (EDIS)
Glossy abelia is a fine-textured, semi-evergreen, sprawling shrub with 1.5-inch-long, red-tinged leaves arranged along thin, arching, multiple stems (Figure 1). It is a hybrid between A. chinensis and A. uniflora. It stands out from other plants because the leaves retain the reddish foliage all summer long, whereas many plants with reddish leaves lose this coloration later in the summer. Considered to be evergreen in its southern range, glossy abelia will lose 50% of its leaves in colder climates, and the remaining leaves will take on a more pronounced red color. Reaching a height of 6 to 10 feet with a spread of 6 feet, the gently rounded form of glossy abelia is clothed from spring through fall with terminal clusters of delicate pink and white, small, tubular flowers. Multiple stems rise from the ground in a vase shape, spreading apart as they ascend into the foliage. This document is Fact Sheet FPS-001, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and and Agricultural Sciences, University of Florida. Publication date: October 1999; reviewed October 2003.